Integrasi Wahyu dan Sains: Telaah Interdisipliner Ayat-Ayat Ilmiah dalam Al-Quran - Rofiqi Akrima Suheri (Arba: Jurnal Studi Keislaman, 2025)
The Quran is not only a source of law and spiritual guidance but also contains signs relevant to modern scientific findings. The background of this research is the interest and challenge in understanding the relationship between the text of Revelation and contemporary scientific theories, especially in the era of technological and scientific progress. This study aims to analyze the verses of the Quran that contain scientific content and examine their suitability with modern scientific theories in an interdisciplinary manner. The method used is qualitative with thematic interpretation analysis (mauḍūʻī) and literature studies from contemporary scientific sources. The results of the study show that several verses of the Quran, such as those related to the creation of the universe, the development of the human embryo, the structure of the earth regarding tectonic plates and weather phenomena, have a significant correlation with modern scientific discoveries, although it is not intended to replace science, but rather to enrich the perspective of faith. In conclusion, the integration of revelation and science is not an attempt to equate the two but rather to show that the Quran supports the search for knowledge holistically, which includes spiritual and rational dimensions. This interdisciplinary approach is expected to open up space for dialogue between scholars and scientists in building a more comprehensive understanding of science.